Creolizing Europe Legacies and Transformations - Gutiérrez Rodríguez, Encarnación (Migrations and Identities, 2015)
Creolizing Europe critically interrogates creolization as the decolonial, rhizomatic thinking necessary for understanding the cultural and social transformations set in motion through trans/national dislocations. Exploring the usefulness, transferability, and limitations of creolization for thinking post/coloniality, raciality and othering not only as historical legacies but as immanent to and constitutive of European societies, this volume develops an interdisciplinary dialogue between the social sciences and the humanities. While not all the contributions in this volume explicitly address Edouard Glissant's approach to creolization, they all engage with aspects of his thinking. All of the chapters explore the usefulness, transferability, and limitations of creolization to the European context. As such, this edited collection offers a significant contribution and intervention in the fields of European Studies, Postcolonial Studies, and Cultural Studies on two levels.